ANALISIS PARAMETER PEMOTONGAN DAN DEBIT PENDINGIN CNC MILLING TERHADAP KEKASARAN PERMUKAAN MENGGUNAKAN BOX BEHNKEN DESIGN - M Yuda Pratama; Ahmad Syuhri; Boy Arief Fachri (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
In the CNC milling machining process, the surface roughness of the workpiece is one of the most important things. By using the box method, the design method is to find parameters that affect the surface roughness of the workpiece. This study aims to determine the effect of feeding speed, feed depth and cooling discharge on the level of surface roughness. And find out which parameters produce the lowest surface roughness value in the CNC milling machining process. From the results of statistical analysis with a significant level in the amount of α = 5% (0.05) obtained feed speed parameters with a value of P> F = 1.79% and depth of infeed with a value P> F = 0.03% proved to have a significant effect on surface roughness, on the parameters cooling discharge proved not to have a substantial impact in surface roughness with a value of P> F = 5.82%. While the optimum combination for the lowest level of surface roughness can be obtained by a combination of 0.18 mm feed depth parameters, 180 mm / minute feeding speed and 10 ml / second cooling discharge with the lowest surface roughness value of 1.027 µm. Keywords: surface roughness, Behnken design box, CNC milling